An Integrative Approach to Operationalizing Strategic Leadership in Banking Institutions - Chishamba, Jealous; Dzingirai, Canicio (Acta Universitatis Danubius. Œconomica, 2024)
This study aimed to operationalize strategic leadership (SL) constructs, assess strategic leaders’ alignment, and prioritize their significance in influencing strategic management practices. Building on SL theories, themes, and metrics within strategic management, the paper integrates diverse scholarly perspectives, addressing gaps in SL operationalization, measurement, and construct development. A semi-systematic and integrative literature review was complemented by empirical research conducted with 13 banks in Zimbabwe, representing at least 80% of the country’s banking sector market share. Purposive sampling yielded a 76% response rate from 380 strategic leaders, and the data was analyzed using descriptive statistics. Six key SL constructs were identified for operationalization: determining strategic direction, leveraging core competencies, developing human and social capital, sustaining an effective corporate culture, emphasizing ethical practices, and establishing strategic controls, with determining strategic direction ranking highest in influencing strategic outcomes. The study highlights the need for a unified SL measurement tool, emphasizing the integration of SL constructs to enhance strategic management practices and improve leadership effectiveness in the banking sector. It offers a holistic, multi-theoretical measurement framework for SL, adaptable across contexts, and provides practical insights for evaluating SL’s role in driving organizational outcomes.